Pendidikan Kesehatan Terhadap Perubahan Pengetahuan Dan Sikap Masyarakat RT 3 Tentang Malaria Di Wilayah Kerja Puskesmas Ayuka - Adolfina Tandilagan; Jane Rate Tasik; Ricky Riyanto Iksan (Universitas Malahayati Lampung, 2022)
ABSTRACT The main health problem in Indonesia. Malaria is one of several vector borne diseases that have the potential to cause extraordinary events and have an impact on health and economic levels. The purpose of this study was to determine the effect of health education on the level of knowledge and attitudes of the community about malaria. The working area of Ayuka Health Center, Mimik Regency. The method used is a quasi-experimental design with one group pretest-posttest design The sample in this study was 60 respondents. Data analysis used Wilcoxson statistical test. Based on the results of the Wilcoxson statistical test on knowledge, p value = 0.000 0.005, it was concluded that there was an effect of counseling on the level of community knowledge about malaria. The results of the Wilcoxson statistical test on the attitude of the patient obtained a value of p = 0.000 (p 0.005) then there was an effect of counseling on the attitude of the patient while the results of the paired t-test statistic on the attitude of the control obtained a value of p = 0.112 (p 0.005)Health workers provide regular counseling to increase community knowledge, motivation from the village side, and community participation in malaria-related activities. Keywords: Knowledge, attitude, malaria ABSTRAK Masalah utama kesehatan di Indonesia. Malaria termasuk salah satu dari sebagian vector borne disease yang berpotensi menimbulkan kejadian luar biasa dan berdampak pada tingkat kesehatan dan ekonomi. Tujuan penelitian ini adalah mengetahui pengaruh penyuluhan kesehatan terhadap tingkat pengetahuan dan sikap masyarakat tentang malaria Wilayah kerja Puskesmas Ayuka Kabupaten Mimik. Metode yang digunakan adalah quasi eksperimen dengan rancangan desain one group pretest-posttest design Sampel dalam penelitian ini adalah 60 responden Analisis data menggunakan uji statistik wilcoxson. Berdasarkan hasil uji statistik wilcoxson terhadap pengetahuan diperoleh nilai p=0,000 0,005 Hasil uji statistik wilcoxson terhadap sikap penderita diperoleh nilai p=0,000 (p0,005) maka ada pengaruh penyuluhan terhadap sikap penderita sedangkan hasil uji statistik paired t-test terhadap sikap kontrol diperoleh nilai p=0,112 (p0,005). Petugas kesehatan memberikan penyuluhan secara rutin untuk meningkatkan pengetahaun masyarakat, motivasi dari pihak desa, dan patisipasi masyarakat dalam kegiatan yang berhubungan dengan malaria. Kata Kunci: Pengetahuan, Sikap, Malaria